2011
DOI: 10.1001/jama.2011.1826
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Resting Heart Rate and Deaths From Ischemic Heart Disease

Abstract: Among men and women without known cardiovascular disease, an increase in RHR over a 10-year period was associated with increased risk of death from IHD and also for all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 31 publications
7
113
0
8
Order By: Relevance
“…Increased resting HR has been shown to be related to cardiovascular mortality, non-cardiovascular mortality, sudden death and coronary artery disease in males and females (22). A study done by Framingham with a follow up of 30 years has shown that resting HR is a risk factor for all-cause mortality and that, additionally, it increases with age and is accompanied by a higher rate of mortality (23).…”
Section: Discussionmentioning
confidence: 99%
“…Increased resting HR has been shown to be related to cardiovascular mortality, non-cardiovascular mortality, sudden death and coronary artery disease in males and females (22). A study done by Framingham with a follow up of 30 years has shown that resting HR is a risk factor for all-cause mortality and that, additionally, it increases with age and is accompanied by a higher rate of mortality (23).…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to disentangle autonomic-dependent and -independent mechanisms related to pulsatile stress and arterial stiffness. This may provide insight into the numerous epidemiological studies that note associations between elevated resting HR and CV mortality independent of traditional risk factors [30][31][32][33][34][35][36][37] and inflammation 38) . Other limitations to this study should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Given that information on pulse and its time-related changes is easy to obtain and follow up, our findings may be useful in identifying asymptomatic people at risk who could benefit from primary prevention measures, for example by vagal stimulation, antiinflammatory or anticholinesterase medications, or by physical activity, that limits increases in cardiovascular mortality risk (28). Future studies may focus on stress-inducible epigenetics (29), microRNA-mediated (21), and genetics changes (30).…”
Section: Significancementioning
confidence: 93%